Malaysian public preferences and decision making for COVID-19 vaccination: A discrete choice experiment - Hoon Shien Teh; Yuan Liang Woon; Chin Tho Leong; Nicholas Yee Liang Hing; Teresa Yong Sui Mien; Laurence S.J. Roope; Philip M. Clarke; Lee-Ling Lim; John Buckell (Elsevier, 2022)
Summary: Background: Low vaccine uptake has the potential to seriously undermine COVID-19 vaccination programs, as very high coverage levels are likely to be needed for virus suppression to return life to normal. We aimed to determine the influence of vaccine attributes (including access costs) on COVID-19 vaccination preferences among the Malaysian public to improve national uptake. Methods: An online Discrete Choice Experiment (DCE) was conducted on a representative sample of 2028 Malaysians. Respondents were asked to make vaccination decisions in a series of hypothetical scenarios. A nested, mixed logit model was used to estimate the preferences for vaccination over vaccine refusal and for how those preferences varied between different sub-populations. The attributes were the risk of developing severe side effects of the vaccine, vaccine effectiveness, vaccine content, vaccination schedule, and distance from home to vaccination centre. Findings: Reported public uptake of COVID-19 vaccination was primarily influenced by the risk of developing severe side effects (b = −1·747, 95% CI = −2·269, -1·225), vaccine effectiveness (b = 3·061, 95% CI = 2·628, 3·494) and its Halal status (b = 3·722, 95% CI = 3·152, 4·292). Other factors such as appointment timing and travel distance to the vaccination centre also had an effect on vaccine uptake. There was substantial heterogeneity in preferences between different populations, particularly for age groups, ethnicity, regions, and underlying health conditions. Interpretation: Perceived effectiveness and side effects are likely to affect COVID-19 vaccine uptake in Malaysia. Halal content is critical to Malays' vaccination choices. Reducing the physical distance to vaccination centres, particularly in rural areas where uptake is lower, is likely to improve uptake. Funding: Ministry of Health Research Grant from the Malaysian government [NIH/800-3/2/1 Jld.7(46), grant reference no: 57377 and warrant no: 91000776].